2022
DOI: 10.24086/cuejhss.v6n1y2022.pp27-34
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to Job Satisfaction Among Workers Living with War Caused Disabilities in ‎Changara District in Mozambique. ‎

Abstract: Job satisfaction of all categories of workers is one of the key antecedents that ensure increased competiveness of organizations. The need to establish factors that impede job satisfaction among people living with war induced disabilities was the main aim of this study. Furthermore, effects of war that adversely affect the attitude of workers with war induced disabilities towards their work were a major driver of this paper. The study employed a pure qualitative research approach where data was collected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The findings are contrary to the provision of the Labour Act (2019) which states that the normal working period was eight hours a day, and that any extra hours should be paid as overtime. Studies (Bell, David & Steffen 2012, Nyanga & Sibanda 2019) also observed that workers need to have decent working hours. Hodzi et al (2021) observed that domestic workers face a plethora of work intensification challenges, exploitation and abuse of domestic workers in rural areas.…”
Section: Work Intensification and Domestic Workersmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings are contrary to the provision of the Labour Act (2019) which states that the normal working period was eight hours a day, and that any extra hours should be paid as overtime. Studies (Bell, David & Steffen 2012, Nyanga & Sibanda 2019) also observed that workers need to have decent working hours. Hodzi et al (2021) observed that domestic workers face a plethora of work intensification challenges, exploitation and abuse of domestic workers in rural areas.…”
Section: Work Intensification and Domestic Workersmentioning
confidence: 99%
“…The study established that workers were working with very tight deadlines and were also overloaded with work. Furthermore, a study by Nyanga & Sibanda (2019) on domestic workers that was carried out in Mozambique also found out that work intensification was rife among informal workers in the developing world. The study further established that work intensification was mainly propelled by the unavailability of a written employment contract.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations